Standardization of Specific and Non-Specific Parameters of Methanol Extract from Poinsettia Red Leaves (Euphorbia pulcherrima Willd.) - Abdillah, Lalu Khairi; Hanifa, Nisa Isneni; Mukhlishah, Neneng Rachmalia Izzatul; Hidayati, Agriana Rosmalina (Jurnal Biologi Tropis, 2024)
The poinsettia red leaves (Euphorbia pulcherrima Willd.) have the potential as antibacterial and antioxidant agents and are widely utilized by the community for wound healing purposes. This research aims to determine the specific and non-specific parameter values of methanol extract from poinsettia red leaves. Samples of poinsettia red leaves were processed into extracts using the maceration method with 96% methanol as the solvent. The extract was standardized by determining specific and non-specific parameters. The test result data were analyzed descriptively in both qualitative and quantitative manners. The standardization results of specific parameters showed the identity of the extract as methanol extract of poinsettia red leaves, with organoleptic properties of a thick greenish-black extract, distinctive poinsettia aroma, and bitter taste. The water-soluble compound content was 51,47% ± 0,437 and ethanol-soluble 61,22% ± 0,117. Results for non-specific parameters indicated drying loss of 12,50% ± 0,419, moisture content of 12,62% ± 0,173, total ash content of 5,25% ± 0,538, acid-insoluble ash of 0,34% ± 0,048, residual solvent 0,00% ± 0,000, total plate count was TFTC (Too Few To Count), and mold and yeast count was 1,5 x 104 colonies/g sample. This research can serve as a reference for determining specific and non-specific parameters of methanol extract from poinsettia red leaves.